Pola Konsumsi Tuak Siwalan (Borassus flabellifer) dan Kaitannya dengan Status Gizi Pria Dewasa di Desa Sidorejo, Kecamatan Pare, Kabupaten Kediri - Puspita, Berliana; Estiningtyas, Dian; Ayok, Lazarus (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
The continuous consumption of fermented beverages such as tuak may pose adverse health effects due to their alcohol content. These effects include impaired consciousness, weight gain, hypertension, reduced immune function, and an increased risk of various degenerative diseases such as cancer, cardiovascular disorders, respiratory problems, and liver dysfunction. This study aims to describe the consumption patterns of tuak siwalan (Borassus flabellifer) and the nutritional status of adult males in Sidorejo Village, Pare Subdistrict, Kediri Regency. This research employed a descriptive approach focusing on two primary variables: the level of tuak consumption and nutritional status. Data were collected using a systematically structured questionnaire. The analysis revealed that the majority of respondents (40.0%) reported low-frequency tuak consumption, while the most prevalent nutritional status was obesity, found in 42.2% of the participants. These findings are expected to serve as a basis for increasing public awareness—particularly among adult males—of the importance of reducing tuak consumption as a preventive effort to improve nutritional status and maintain overall health, given their strategic role in family resilience.